2015
DOI: 10.1063/1.4913446
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements of the magnetocaloric effect in pulsed magnetic fields: The example of the Heusler alloy Ni50Mn35In15

Abstract: We have studied the magnetocaloric effect (MCE) in the shape-memory Heusler alloy Ni 50 Mn 35 In 15 by direct measurements in pulsed magnetic fields up to 6 and 20 T. The results in 6 T are compared with data obtained from heat-capacity experiments. We find a saturation of the inverse MCE, related to the first-order martensitic transition, with a maximum adiabatic temperature change of ∆T ad = −7 K at 250 K and a conventional field-dependent MCE near the second-order ferromagnetic transition in the austenitic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(27 citation statements)
references
References 16 publications
2
25
0
Order By: Relevance
“…A rate of about 20 T s −1 can be realized by a pneumatic sample holder moving the magnetocaloric material in a static magnetic field . Fast field‐sweep rates of up to 1 kT s −1 are achieved in pulsed magnetic fields …”
Section: Dynamical Effects At Magnetostructural Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A rate of about 20 T s −1 can be realized by a pneumatic sample holder moving the magnetocaloric material in a static magnetic field . Fast field‐sweep rates of up to 1 kT s −1 are achieved in pulsed magnetic fields …”
Section: Dynamical Effects At Magnetostructural Transitionsmentioning
confidence: 99%
“…In the following, DT ad measurements with field-sweep rates in the range between 10 mT s À1 and 1kTs À1 are compared to study the effects of different rates on the MCE in Ni 50 Mn 35 In 15 , [43,222] La(Fe,Si,Co) 13 , [223] and Mn 3 GaC. [171] The generation of magnetic-field-sweep rates in these ranges requires the use of different devices and magnets.Alow fieldsweep rateo fa pproximately 10 mT s À1 can be generated by using as uperconducting magnet.…”
Section: Dynamical Effects At Magnetostructuralt Ransitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed that Ni 50 Mn 35 In 15 exhibits an inverse magnetocaloric effect of −7 K, in a field change of 6 T, that arises from a change in the entropy due to the magneto-structural transition [5]. At 4 K the application of a 20 T field still induces the martensitic transition and, besides the change in magnetic moment, leads to a relative change in length of 0.8% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Properties such as shape memory [1,2], magnetic superelasticity [3], magnetocaloric [4,5] and barocaloric effects [6] have attracted considerable attention due to their potential use in applications. However, the lattice dynamics and its coupling to magnetic properties have been studied relatively little in these alloys.…”
Section: Introductionmentioning
confidence: 99%